Biomass Estimation Model in Revegetation Area of Nickel Post-Mining - Witno Witno; Nining Puspaningsih; Budi Kuncahyo (Department of Forest Resources Conservation and Ecotourism - IPB University, 2018)
Deforestation and forest degradation are one of the most crucial issues in the forestry sector. The impact of deforestation and forest degradation due to the opening of forest areas for mining activities that causes damage to sustainable forest ecology. This condition requires companies as miners to carry out revegetation activities in post-mining areas to restore forest existence. PT. Vale of Indonesia (PTVI) is a nickel mining company located in Sorowako, South Sulawesi Province, which has carried out revegetation activities and is considered quite successful. This assessment has not included biomass as an indicator of forest productivity. Biomass is one of the determinants of forest productivity in post-mining areas needs to be further investigated to maximized revegation management. The objective of this study was to measure and construct a model for estimating biomass in the revegetation of the post-mining area in PTVI. The results of this study obtained a regression model of the rank as a biomass estimator in the revegetation of the post-mining area in PTVI. The form of the selected model equation is Y= 2,59505E-13 X1 2,489 X2 3,645. The independent variable is X1 = DVI (vegetation index) and X2 = C% (percentage of canopy). The regression model chosen has a determination coefficient of 70,60% and a standard deviation of -0,33528. Keywords: biomass, post-mining, regression model, revegetation